2018
DOI: 10.1037/hea0000559
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the role of obesity in the association between childhood trauma and inflammation during pregnancy.

Abstract: Exposure to childhood trauma, particularly emotional abuse, physical abuse, and emotional neglect, is associated with inflammation in pregnant women. Obesity served as 1 pathway by which physical abuse contributed to elevations in serum CRP and IL-6. Interventions targeting maternal obesity prior to pregnancy may help mitigate the effects of childhood trauma on perinatal health. These findings have relevance for understanding biological and behavioral pathways by which early life exposures contribute to matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 78 publications
(120 reference statements)
3
16
1
Order By: Relevance
“…Consistent with the larger literature (Miller et al, 2017; Mitchell et al, 2018; Walsh et al, 2016), the current study provides further evidence that adversities experienced during childhood and adulthood are associated with elevated inflammatory markers during pregnancy. Specifically, bivariate correlations revealed that a history of childhood abuse was positively associated with both CRP and IL-6 in a sample of pregnant women, while current SES was negatively associated with both CRP and IL-6.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with the larger literature (Miller et al, 2017; Mitchell et al, 2018; Walsh et al, 2016), the current study provides further evidence that adversities experienced during childhood and adulthood are associated with elevated inflammatory markers during pregnancy. Specifically, bivariate correlations revealed that a history of childhood abuse was positively associated with both CRP and IL-6 in a sample of pregnant women, while current SES was negatively associated with both CRP and IL-6.…”
Section: Discussionsupporting
confidence: 90%
“…These results also extend upon studies that have demonstrated a history of childhood abuse to be associated with elevated CRP in non-pregnant individuals after adjusting for SES (Baumeister et al, 2016; Coelho et al, 2014; Danese et al, 2007). Although empirical studies in pregnant women are limited, these data support prior research from our group linking childhood abuse history to elevated CRP, but not IL-6, after adjusting for current SES within a different and smaller cohort of 77 women (Mitchell et al, 2018). In contrast to previous research (Baumeister et al, 2016), the association between childhood abuse history and IL-6 was not replicated in our sample, further adding to mixed findings (for review see Coelho et al, 2014).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Most likely, pregnancy impacted cytokine response to stress; a similar study that utilized the TSST found that pregnant women had a dampened IL-6 response to the TSST compared with non-pregnant women (Christian et al, 2013). However, our result is similar to findings in which history of childhood abuse was not directly associated with baseline IL-6 during pregnancy, but mediated by another factor (in that case, BMI) (Mitchell et al, 2018). While not powered for a mediation analysis, exploratory analyses indicated that dietary intake of ω-3 PUFAs, particularly DHA, was associated with a dampened inflammatory response to acute stress among high ACE women.…”
Section: Discussionsupporting
confidence: 90%
“…Obesity, conceptualized as a physiological stress, has been linked to considerable increases in circulatory inflammatory markers, particularly IL-6, throughout pregnancy and postpartum. Moreover, psychological stress and obesity may interact synergistically, resulting in more pronounced effects among women with both risk factors (Mitchell and Christian 2018). In addition, obesity has been observed to increase the risks of gestational hypertension and gestational diabetes via inflammatory pathways.…”
Section: Pregnancymentioning
confidence: 99%